Pengaruh Pelatihan Model POT EMAS terhadap Kemampuan Keluarga Merawat Lansia dengan Diabetes Melitus - Tien Hartini; Yeti Resnayati; Agus Sri Sukoco; Supriadi; Raden Siti Maryam (Universitas Bengkulu, 2023)
In general, many elderly people complain of various kinds of symptoms that are felt due to a decrease in body condition. Apart from being affected by the decline in the elderly, it is also influenced by a lack of knowledge, attitudes, and family behavior in caring for the elderly. This study aims to obtain an overview of the effect of the Energetic, Helpful, Active and Patient Parent Assistance Model, abbreviated as